Impact of Telepharmacy on Medication Adherence and Patient Satisfaction: A Literature Review - Hannah Yusriyyah; Rano Kurnia Sinuraya; Auliya Abdurrohim Suwantika (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Background: Technology has transformed patient care, with telepharmacy emerging as a major advancement. The use of telepharmacy expanded rapidly during and after the COVID-19 pandemic, ensuring continuity of medical care when in-person access was limited. It effectively addresses challenges such as social isolation, restricted facility visits, and the lack of face-to-face consultations. Clinical advantages include improved access to healthcare, reduced costs, higher patient satisfaction, enhanced counseling, and better therapy adherence.Objectives: This literature review aims to the impact of telepharmacy services on medication adherence and patient satisfaction across diverse healthcare settings and patient populations.Methods: A literature search was conducted in PubMed and Scopus using the Boolean operator AND and the keywords